2021
DOI: 10.1542/peds.2021-051959
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Age, Parent Education, and Education in Adulthood

Abstract: BACKGROUND: Adults born preterm (<37 weeks) have lower educational attainment than those born term. Whether this relationship is modified by family factors such as socioeconomic background is, however, less well known. We investigated whether the relationship between gestational age and educational attainment in adulthood differed according to parents’ educational level in 4 Nordic countries. METHODS: This register-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
3
1
Order By: Relevance
“…Also, another study on vaginal delivery with and without anesthesia showed that the study groups in the second phase of labor were not significantly different but were different from each other in terms of the active labor phase. [ 26 27 28 ] It is noteworthy that the results of this study on the second stage of labor were not consistent with the results of our study, but the results of the active phase of labor in this study were consistent with our findings.…”
Section: Discussioncontrasting
confidence: 70%
“…Also, another study on vaginal delivery with and without anesthesia showed that the study groups in the second phase of labor were not significantly different but were different from each other in terms of the active labor phase. [ 26 27 28 ] It is noteworthy that the results of this study on the second stage of labor were not consistent with the results of our study, but the results of the active phase of labor in this study were consistent with our findings.…”
Section: Discussioncontrasting
confidence: 70%
“…Parental education and socioeconomic status have been described as risk factors for the poorer neurodevelopmental outcome of preterm infants. In a recent study, parental educational level did not modify the relationship between gestational age and educational attainment in adulthood, although across all gestational age groups up to term age, lower parental education level was associated with lower educational attainment at 25 years [23].…”
Section: Family Situationmentioning
confidence: 79%
“…Other factors beyond gestational age impact the prognosis, including baseline factors, such as antenatal steroids [18,19], gender [20,21], birth weight [21,22], possibly socioeconomic status [23] and factors not attributable to the individual case but the centre practice [24] and attitudes [25].…”
Section: Introductionmentioning
confidence: 99%
“…independently graded evidence according to the GRADE handbook 33 . The strength of evidence was initially set as low and was rated up for 1) large effect sizes (Relative risk <0.5 or >2, and SMD<-0.25 or >0.25), 2) where a dose-response relationship was shown, and 3) effect of plausible residual confounding (such as parental education level ) 34 was considered. The strength of evidence was classified as very low, low, moderate, or high quality.…”
Section: Data Synthesismentioning
confidence: 99%